Commensalistic institutions and value conflicts: the World Trade Organization and global private food standardsa. (17th January 2014) - Botterill, Linda Courtenay; Daugbjerg, Carsten
<x content-type="archive" xml:space="preserve">Abstract</x> An important outcome of the Uruguay Round of multilateral trade negotiations was the Agreement on the Application of Sanitary and Phytosanitary Measures (SPS Agreement). This was set up to discipline the use of national food safety and animal and plant health regulations and to prevent their emergence as technical barriers to trade. The Agreement privileges free trade and scientific evidence, thus excluding many ethical considerations from the regulations that national governments can enact in relation to production methods in the agri-food chain. Autonomously from the SPS Agreement, a number of global private standard schemes have been developed that have incorporated values rejected by the SPS Agreement. This paper examines the relationship between the Agreement and the private standards and argues that this case highlights a gap in the institutional literature with respect to parallel institutions emerging autonomously from the primary institution to embody values excluded by the latter. We adopt the term commensalism for these previously undescribed relationships.